COVID-19 and implementation of online learning in Ghana: Perspectives of undergraduate students in higher education institutions - Tsevi, Linda (American Journal of STEM Education, 2025)
The COVID-19 pandemic affected teaching and learning in higher education institutions globally, and Ghana was no exception. Educational institutions had to adapt to new models of teaching. Using the connectivism learning model and a purposive sample of 18 undergraduate students from three public and three private higher education institutions, this study explored perspectives on the institutional adaptation of online learning during the pandemic. The findings of the study indicate that although majority of higher education institutions did not have adequate structures to transition teaching and learning online smoothly, they could adapt to available technology that suited majority of students. There is a call for promulgating a policy to standardize online learning delivery in Ghana.